Epilepsy as Central Nervous System Involvement in Patient with ANCA-Associated Vasculitis: A Case Report - de Jesús, Martínez Camacho Roberto; Murillo Reyna, Héctor; Martínez Camacho, Lilia Itzel; Ruíz Gómez, María Fernanda; Sandoval Correa, Santiago; Linaldi Sierra, Hayil; González Orozco, Francisco Alejandro; Nieves Paredes , Eduardo; Vela Rivera, Marcos; Aguirre Gonzalez, Consuelo Alejandra (International Journal of Medical Science and Clinical Research Studies, 2024)
Central nervous system (CNS) involvement by antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a rare presentation. The affected nerve structure determines the symptoms of AAV. Presentation as seizures can make early diagnosis difficult by necessitating the ruling out of other etiologies, which increases mortality in these patients. Serological and imaging studies facilitate the identification of AAV and initiation of timely treatment focused on remission of the autoimmune pathology. We present the case of a young female patient who, after diagnosis with AAV by renal biopsy, presented with several epileptic seizures. With angioresonance, we evidenced vascular involvement and began remission treatment with an adequate resolution of the seizures.